Environmentally sound wood harvesting in Omo forest reserve Ogun State Nigeria (2011)
The depletion of the notion's forest reserves through improper wood harvesting methods is alarming and threatening. The trend has been giving all stakeholders serious concern and it has become imperative for a research to be undertaken to find an alternative and better logging method that is environmentally sound and acceptable. A work study was therefore carried out to assess and compare damages and productivity in both Conventional Logging System (CLS) and Reduced Impact Logging (RIL) in a Nigerian forest reserves. Data for the study were collected on damages to residual plants and productivity per time per harvesting method using a time study and work analysis approach. The data so collected were then subjected to both descriptive and inferential statistical processing. Results show that RIL can reduce damages to residual stand by close to 50 percent when compared to CLS. Result of time study show that the average time required for felIing of a tree in RIL and CLS are 9.91 and 7.52 minutes respectively. The productivity in RIL is 78.58m3/hour while it is 89.25m3/hour for CLS. Statistical analyses show that productivity in RIL is not significantly different from productivity in CLS but largely depends on the volume of the harvested tree. It is recommended that RIL be adopted and encouraged in wood exploitation to promote environmentally sound wood exploitation in Nigerian forest estates.